All Days 2008
DOI: 10.2118/116575-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Minimum Tested Volume from the Deconvolution of Well Test Pressure Transients

Abstract: Radius of investigation and tested volume are important results of well test analysis which can make or break future field development. Currently, their evaluation is either approximate or relies on a complete analysis of the transient pressure response using an appropriate model. A new method is proposed that uses the deconvolved derivative response to determine a minimum tested volume. It is accurate and does not rely on further transient analysis. The method can be applied to any oil or ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Recently, Whittle and Gringarten (2008) suggested using the intersection as shown in Fig. 7 for calculating the radius of investigation from derivative curve.…”
Section: Radius Of Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Whittle and Gringarten (2008) suggested using the intersection as shown in Fig. 7 for calculating the radius of investigation from derivative curve.…”
Section: Radius Of Investigationmentioning
confidence: 99%
“…Therefore, if a unit slope on the derivative plot due to a no-flow boundary condition is available, one should use either Eq. 12 (Whittle and Gringarten, 2008) or Eq. 13, particularly with noise derivatives.…”
Section: Radius Of Investigationmentioning
confidence: 99%
“…Daungkaew et al [4] derived a calculation formula of the radius of investigation of a vertical well in a homogeneous reservoir with a closed boundary. Whittle and Gringarten [5] suggested that the radius of investigation can be calculated using the intersection of the unit slope representing pseudo-steady flow and the horizontal slope corresponding to infinite radial flow on the pressure derivative curve. By considering oil production, reservoir thickness and pressure gauge resolution, Kuchuk [6] proposed a calculation formula of the radius of investigation of a radial cylindrical oil reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Then the deterministic (volumetric) estimates of hydrocarboninitially-in-place based on the resulting geometry (from the numerical simulation) are compared with estimates of minimum tested volumes derived using the method of Whittle et al, 2008. In the end it is shown that for single-phase systems with small pressure drops, the simple 2D numerical simulator can aid in the reduction of geological uncertainty thereby solving a complex problem through relatively simpler means.…”
mentioning
confidence: 99%
“…Top structure isochore map used for numerical simulation showing the active fault used for fault seal sensitivity.MINIMUM TESTED VOLUME Using the method suggested byWhittle et al (2008), the minimum tested volume during the test is estimated.…”
mentioning
confidence: 99%